Bleeding Disorders in Women and Girls: State of the Science and CDC Collaborative Programs. - Byams, Vanessa R.; Miller, Connie H.; Bethea, Fiona M.; Abe, Karon; Bean, Christopher J.; Schieve, Laura A. (Journal of Women's Health (15409996), 2022)
Women and girls with bleeding disorders experience abnormal and excessive bleeding that can negatively impact their overall health and quality of life. In this report, we provide an overview of the biology, types, clinical care, and state of the science related to bleeding disorders in girls and women and describe Centers for Disease Control and Prevention (CDC) activities related to (1) surveillance of bleeding disorders in women; (2) scientific review, research, and collaboration to inform health care gaps in identifying and caring for women with bleeding disorders; and (3) development of health promotion and education programs to bring awareness about bleeding disorders to both women and girls in the population at large and various health care providers who care for women. Findings generated from surveillance and research activities inform the development of new public health programs aimed at improving diagnostic and health care services and empowering women with bleeding disorders with the knowledge they need to navigate a complex health care system with the need for specialty care services. Additional work is needed to improve provider awareness and understanding of the unique needs of women and girls with bleeding disorders to achieve appropriate care and treatment and ensure optimal outcomes and quality of life.